Redesigning animal agriculture : the challenge of the 21st century/ (Acc. 5033) - Swain, D.L. (Wallingford, Oxfordshire, UK CAB International, 2007)
Based on papers presented at the third Horizons in livestock sciences conference series
Focusing on livestock production systems, this text addresses how the growing diversity of global food demands will be met in the future, providing insights into new and emerging scientific areas and the implications for addressing global drivers for change. The book covers ethical, philosophical and systemic considerations, the impact of genomics on livestock production, the holistic systems perspective, the complex systems approach using stochastic modelling methods, and how all these factors can be linked to achieve sustainable outcomes.
Keywords: livestock; livestock farming; animal production; animal breeding; ethics; agricultural production systems